IL-17A in the Psoriatic Patients' Serum and Plaque Scales as Potential Marker of the Diseases Severity and Obesity. (5th June 2020) - Michalak-Stoma, Anna; Bartosińska, Joanna; Kowal, Małgorzata; Raczkiewicz, Dorota; Krasowska, Dorota; Chodorowska, Grażyna
Abstract : The aim of the study was to evaluate concentrations of IL-17 in the serum and plaque scales of psoriatic patients. We analyzed their association with the clinical activity of the disease and with body mass index (BMI). Demographic data, medical history, serum, and scale from psoriatic plaques for assessment of IL-17 were collected from all the participants. The disease severity was assessed with PASI (Psoriasis Area and Severity Index), BSA (Body Surface Area), PGA (Physician Global Assessment), NAPSI (Nail Psoriasis Severity Index), and DLQI (Dermatology Quality of Life Index) scores. Obesity was diagnosed by calculating body mass index. Serum and scale concentration of IL-17 was determined with Human IL-17A High Sensitivity ELISA kit and Human IL-17 ELISA kit. In the psoriatic patients, BMI was statistically significantly higher than in the control group. Most of the patients presented BMI higher than normal. Our study confirms that overweight is a problem among psoriatic patients. A significant positive correlation between the IL-17 serum and scale concentrations and psoriasis severity indicates that IL-17 can be used as the marker of disease severity. More data from human studies can be crucial for understanding that relationship between IL-17, psoriasis, and obesity.